AL-KUTUB AL-MU'ALLAFAH FI TA'LIM AL-LUGHAT WA MANAHIJUHA HATTA AWAKHIR AL-QARN AL-TSALITS 'ASYAR AL-HIJRI - Basiron Bin Abdullah (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2016)
The research seeks to examine the books composed in language teaching in the Arab heritage until the third century AH, detect the most important characteristics of these compositions and identify the most curricula in the teaching of languages. The research analyzed two essential books, i.e. Revealed Suspicions about Asami Books and the Arts by Haji Khalifa, and Albulgh in the Assets of the Language by Mr. Mohammad Khan Alguenoja. It focused on three languages: Persian, Turkish and Arabic. Therefore, the researcher categorized studying these languages ​​into four groups. They are the first group composed in Arabic to study Persian; the second books composed in Farsi to study Arabic; the third books composed in Turkish for the study of Persian; and the fourth books pointing at Persian instructions composed in Farsi. The relationship between the Arabs and Persians and the Persians and Turks with reference to the history of linguistic relations among them. The researcher noted that the method in teaching these languages ​​has focused on the basics of the language by Kalpde to identify the name, action and the source, and also found there are dictionaries of linguistic help in the educational process.DOI : 10.15408/a.v3i1.3023